Uncertainty in Mechanical Engineering III - Peter F. Pelz; Peter Groche (Trans Tech Publications Ltd, 2018)
Selected, peer reviewed papers from the 3rd International Conference on Uncertainty in Mechanical Engineering (ICUME 2018), November 15 - 16, 2018, Darmstadt, Germany